2019
DOI: 10.3390/molecules24193590
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Langmuir Monolayers of Perfluorinated Fatty Acids: Evidence of a New 2D Smectic C Phase

Abstract: Due to the characteristic chain rigidity and weak intermolecular interactions of perfluorinated substances, the phase diagram of Langmuir monolayer formed by perfluorinated molecules has been interpreted so far as displaying only two phases, a 2D gas (G) and a liquid condensed (LC). However, in this work, we presented Grazing Incidence X-ray Diffraction measurements, which exhibit two diffraction peaks on the transition plateau: One is the signature of the hexagonal structure of the LC phase, the second one is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…As in our previous study of fluorinated alcohols, the terminal –CF 2 CH 2 OH segment was modelled after the work of Duffy on trifluoroethanol [ 57 , 58 ], adjusting the partial charge of the fluorinated carbon to keep the electrical neutrality of the molecule. The model for the remainder of the perfluorinated tail is based on the parameters described by Watkins and Jorgensen [ 59 ], with adjustments to the atomic partial charges and to the dispersive energy parameter ( ε ) of fluorine atoms to account for the long CF chains, as described in previous work [ 12 ]. The rigid 3-site SPC/E model was used for the water molecules [ 60 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As in our previous study of fluorinated alcohols, the terminal –CF 2 CH 2 OH segment was modelled after the work of Duffy on trifluoroethanol [ 57 , 58 ], adjusting the partial charge of the fluorinated carbon to keep the electrical neutrality of the molecule. The model for the remainder of the perfluorinated tail is based on the parameters described by Watkins and Jorgensen [ 59 ], with adjustments to the atomic partial charges and to the dispersive energy parameter ( ε ) of fluorine atoms to account for the long CF chains, as described in previous work [ 12 ]. The rigid 3-site SPC/E model was used for the water molecules [ 60 ].…”
Section: Methodsmentioning
confidence: 99%
“…On the contrary, studies of Langmuir films of fluorinated amphiphiles have been less systematic and scarcer. Nonetheless, there have been important efforts to describe and interpret phase transitions and molecular organization in Langmuir films of several perfluorinated acids, alcohols and phospholipids [ 10 , 11 , 12 , 13 , 14 ], as well as amphiphiles with more complex molecular structure such as fluorinated bolaamphiphiles [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The critical micelle concentration for PFOA also falls below the solubility limit, and X-ray reflectivity measurements showed that the thickness of a perfluorinated carboxylic acid layer corresponds to a monolayer state of the film. 23 …”
mentioning
confidence: 99%
“…In fact, grazing incidence X-ray diffraction studies of monolayers of perfluorinated carboxylic acids have revealed tight hexagonal packing of molecules with their long axes nearly perpendicular to the water surface and the coexistence of crystalline and dilute disordered phases. 23 , 31 …”
mentioning
confidence: 99%